Alternative Splicing of MoPTEN Is Important for Growth and Pathogenesis in Magnaporthe oryzae - Wang, Shaowei; Liang, Hao; Wei, Yi; Zhang, Penghui; Dang, Yuejia; Li, Guihua; Zhang, Shi-Hong (Frontiers in Microbiology, 2021)
Human PTEN, a dual-phosphatase tumor suppressor, is frequently dysregulated by alternative splicing. Fungi harbor PTEN homologs, but alternative splicing of fungal PTENs has not been reported as far as we know. Here, we described an alternative splicing case in the PTEN homolog of Magnaporthe oryzae (MoPTEN). Two splice variants of MoPTEN were detected and identified, which are resulted from an intron retention and exclusion (MoPTEN-1/2). Both proteins were different in lipid and protein phosphatase activity and in expression patterns. The MoPTEN deletion mutant (ΔMoPTEN) showed the defects in conidiation, appressorium formation, and pathogenesis. ΔMoPTEN could be completely restored by MoPTEN, but rescued partially by MoPTEN-1 in the defect of conidium and appressorium formation, and by MoPTEN-2 in the defect of invasive development. Assays to assess sensitivity to oxidative stress reveal the involvement of MoPTEN-2 in scavenging exogenous and host-derived H2O2. Taken together, MoPTEN undergoes alternative splicing, and both variants cooperatively contribute to conidium and appressorium development, and invasive hyphae growth in plant cells, revealing a novel disease development pathway in M. oryzae.